Future challenges and developments in the design of steel structures – an Australian perspective. (13th September 2017) - Rasmussen, Kim J.R.; Zhang, Hao
ABSTRACT: The paper provides an overview of recent advances towards developing the Direct Design Method (DDM) and its implementation in design standards. The DDM allows design by advanced structural analysis (GMNIA) requiring no recourse to a design standard for checking member or cross‐sectional strength. As the capability of structural analysis programs increasingly incorporate both geometric and material nonlinear effects, and as standard desktop computers have become sufficiently powerful to run GMNIA analysis, the DDM is poised to become the future method of design. The paper outlines the system reliability framework that underpins the DDM and the calibration of the Method for 2D and 3D hot‐rolled structural frames as well cold‐formed structural frames featuring cross‐sectional instability. The system reliability implications of the DDM and load and resistance factor design (LRFD) are discussed. The paper also discusses the philosophy of teaching steel structural design and argues this is most rationally and efficiently undertaken using the DDM. Lastly, the paper comments on ongoing and future developments on the DDM including the implementation of the method in design practice.